One new Encyonema Kützing (Bacillariophyta, Cymbellaceae) species from the Liujiang River, Guangxi Zhuang Autonomous Region, China - Guo, Ji-Shu; Zhang, Yun; Kociolek, John Patrick; Li, Yan-Ling (Phytotaxa, 2025)
Encyonema liujiangensis sp. nov., a new freshwater diatom species was found on stones of Liujiang River, Guangxi Zhuang Autonomous Region, China. The morphological features of this new species are presented based on light and scanning electron microscopy. E. liujiangensis sp. nov. exhibits the typical characteristics of the genus, such as dorsiventral valves and the direction of deflection of the external distal raphe ends relative to the dorsal margin. The new species closely resembles E. malaysianum and E. chebalingense and shares certain morphological features with some other members in this genus. However, a distinct combination of morphological features justifies identifying E. liujiangensis sp. nov. as a new species: 1) the outline of valves being distinctly dorsiventral with acutely rounded ends, 2) the narrower valve width, 3) the higher stria density at the ends. Brief notes on the accompanying diatom flora and its ecological characteristics are included.